One-year outcomes of polymer-free amphilimus-eluting stents versus durable polymer zotarolimus-eluting stents in patients with diabetes mellitus: a meta-analysis - Hong Wang; Xiaoya Xie; Quannan Zu; Ming Lu; Rongfa Chen; Zhiren Yang; Yongqiang Gao (Cardiovascular Diabetology, 2022)
Abstract Background Diabetes mellitus (DM) and cardiovascular diseases often co-exist. Today, percutaneous coronary intervention (PCI) is the preferred revascularization procedure for majority of patients with coronary artery disease. Polymer-free amphilimus-eluting stents (AES) represent a novel elution technology in the current era of drug-eluting stents. In this analysis, we aimed to systematically compare the cardiovascular outcomes which are associated with polymer-free amphilimus-eluting stents (AES) versus the durable polymer zotarolimus-eluting stents (ZES) for the treatment of patients with DM. Methods Http://www.ClinicalTrials.gov, EMBASE, Web of Science, MEDLINE, Cochrane database and Google Scholar were searched for publications comparing polymer-free AES versus durable polymer ZES in patients with DM. Selective cardiovascular outcomes were assessed. Statistical analysis was carried out by the latest version of the RevMan software. Risk ratio (RR) with 95% confidence interval (CI) was used to represent the data analysis. Results Four studies with a total number of 1795 participants with DM whereby 912 patients were assigned to be revascularized by the polymer-free AES and 883 patients were assigned to be revascularized by the durable polymer ZES were included in this analysis. In patients with DM, at one year, polymer-free AES were associated with significantly lower risk of major adverse cardiac events (MACEs) (RR: 0.69, 95% CI: 0.54–0.88; P = 0.002) and target lesion failure (TLF) (RR: 0.66, 95% CI: 0.48–0.91; P = 0.01) compared to durable polymer ZES. However, there was no significant change in all-cause mortality (RR: 0.79, 95% CI: 0.51–1.22; P = 0.28), cardiac death and the other cardiovascular outcomes. Similar risk of total stent thrombosis (RR: 1.13, 95% CI: 0.60–2.13; P = 0.70), including definite stent thrombosis (RR: 1.12, 95% CI: 0.38–3.31; P = 0.84), probable stent thrombosis (RR: 0.87, 95% CI: 0.37–2.09; P = 0.76), possible stent thrombosis (RR: 1.19, 95% CI: 0.50–2.87; P = 0.69) and late stent thrombosis (RR: 1.00, 95% CI: 0.17–5.72; P = 1.00) as between polymer-free AES and durable polymer ZES in patients with DM. Conclusions At 1 year follow-up, polymer-free AES were associated with significantly lower MACEs and TLF compared to durable polymer ZES in these patients with DM, without any increase in mortality, stent thrombosis and other cardiovascular outcomes. However, this analysis is only based on a follow-up time period of one year, therefore, future research should focus on the long term follow-up time period.